Simulation of the mechanical properties of carbon nanotubes under the influence of doping [electronic resource] - Vahid Ahani, 1988-; Oschner, Andreas (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014